PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF MENGGUNAKAN PENDEKATAN REALISTIK PADA MATA KULIAH STATISTIKA MATEMATIKA I - Sutrisni Andayani; Jazim Jazim (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
The purpose of this research is developing the cooperative model by using the realistic approach in Mathematic Statistics I. As the form of development and research, collecting data done through  observation method, questionnaire, interviewing, and a test. The step of  this research are introduction study, plan, develop and evaluation. Based on the introduction study, was developed of cooperative instructional and realistic approach instructional. Syntax in cooperative instructional model done by realistic approach  is running well and  there are  increasing of activity, response and student’s learning achievement, and difference of  probability explanation using realistic approach. Syntax instructional of the model are 1) material explanation 2) group discussion by using context, model, alternative in problem-solving and finally concluding of all, 3) the group member is given the quiz individually, and 4) the score and reward are given to the group. Keywords: cooperative instructional model, mathematic statistics I, realistic approach